Colonización de macroinvertebrados acuáticos en tres tipos de sustratos artificiales, en un río tropical - Quesada-Alvarado, Francisco (2020)
Introduction: Different methodologies exist for sampling aquatic macroinvertebrates, however, some of these (e.g., kick-net, Surber) are not well suited for deep, contaminated rivers or rivers with presence of crocodiles, which represent a risk to the person who must take the sample. One alternative is to use artificial substrates. The use of artificial substrates to evaluate the aquatic macroinvertebrate biodiversity in wetlands has been studied previously in Costa Rica, but no research has been conducted to determine which types of substrates are most effective. The present study aimed to evaluate the effectiveness of three artificial substrates (i.e., stones, leaves and wood). Methods: Samples of the three substrates were taken bi-monthly between 2013 and 2017 in four sites of the Parismina River. A Kruskal-Wallis test was applied to determine differences between the macroinvertebrate abundance among substrate type. Beside to determine if there is a difference between substrates per site, a two-way PERMANOVA test was applied and a multiple correspondence analysis was used to correlate the substrate type with the macroinvertebrate community. Results: A total of 1  159 organisms were collected, with Diptera and Ephemeroptera being the most abundant. Wood and leaves were the substrates with greatest biodiversity and abundance of organisms; in addition the two sites with greatest vegetation were the most diverse. Conclusions: Most of the organisms were registered on any of the three types of artificial substrates, thus we recommend the joint use of the three types of substrates for biomonitoring or taxa richness studies.